2019
DOI: 10.1021/acs.nanolett.9b01770
|View full text |Cite
|
Sign up to set email alerts
|

Sealing Graphene Nanodrums

Abstract: Despite theoretical predictions that graphene should be impermeable to all gases, practical experiments on sealed graphene nanodrums show small leak rates. Thus far, the exact mechanism for this permeation has remained unclear, because different potential leakage pathways have not been studied separately. Here, we demonstrate a sealing method that consists of depositing SiO 2 across the edge of suspended multilayer graphene flakes using electron beam-induced deposition. By sealing, leaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 23 publications
4
66
1
Order By: Relevance
“…A further requirement on membrane properties in many NEMS sensors, such as in some pressure sensor, is that the membrane may need to be hermetically sealed, such that the pressure in the reference cavity is constant and gas leakage is negligible during its lifetime [21]. Despite the impermeability of graphene for gases [20], [22] it was found that gas can leak via the interface between the substrate and the graphene.…”
Section: Mechanical Properties Of Suspended 2d Materials Membranes Andmentioning
confidence: 99%
“…A further requirement on membrane properties in many NEMS sensors, such as in some pressure sensor, is that the membrane may need to be hermetically sealed, such that the pressure in the reference cavity is constant and gas leakage is negligible during its lifetime [21]. Despite the impermeability of graphene for gases [20], [22] it was found that gas can leak via the interface between the substrate and the graphene.…”
Section: Mechanical Properties Of Suspended 2d Materials Membranes Andmentioning
confidence: 99%
“…Graphene films have raised lot of attention in the past 15 years due to their outstanding material properties. In particular, given the combination of mechanical and electrical properties, these films are very promising for micro-and nano-electromechanical systems (MEMS & NEMS) and their applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . Most of the studies on graphene are usually performed on supporting substrates such as SiO 2 /Si.…”
mentioning
confidence: 99%
“…Graphene grown by chemical vapor deposition (CVD) is a strong candidate for realizing next-generation sensor devices 1 . Its hermeticity [2][3][4] and superior mechanical [5][6][7] and electrical 8 properties have enabled various types of gas pressure sensors. In most conventional pressure sensors, the pressure is determined from the deflection of a membrane due to the pressure difference between ambient gas and gas in a hermetically sealed reference cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In capacitive graphene pressure sensors, the deflection is readout by measuring the capacitance between the graphene membrane and a reference electrode [9][10][11][12] . As the pressure-induced deflection increases the mechanical stress and tension in the membrane, it can be measured using the piezoresistive effect [13][14][15] and can be probed via the mechanical resonance frequency 2,3,16 . In contrast, graphene squeeze-film pressure sensors 17 and Pirani pressure sensors 18 do not require a hermetic reference cavity and operate at small deflection, which can be beneficial for their operation range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation